Analysis Of The Effect Of Current Ratio, Debt To Equity Ratio, Total Asset Turnover, And Firm Size On Return On Assets - M. Jusman Syah; Aris Wahyu Kuncoro; Hasan Ipmawan; Dwi Kristanto; Koen Hendrawan; Pambuko Naryoto (Pusat Riset dan Inovasi Nasional, 2023)
Abstract, This research is to determine the effect of the current ratio, debt to equity ratio, total asset turnover, and firm size on the return on assets of pharmaceutical companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The samples used in this study were 10 pharmaceutical companies. The sampling technique used purposive sampling method. The analytical tool used is multiple linear regression analysis. The results of this study indicate that the Current ratio, which is measured using a comparison of current assets with current liabilities, has no effect on profitability. The Debt to Equity Ratio, which is measured using a comparison between debt and capital, has a negative and significant effect on the return on assets. Total Asset Turnover as measured using a comparison between total sales and total assets has no significant effect on return on assets. Firm Size or company size as measured using total assets has no effect on return on assets.